Perception of General and Dental health hazards among Ragpickers in Lahore, Pakistan - Jawad, Imran; Ali, Nimra; Tahir, Izah; Khan, Nissa; Wamik Ehsan; Khan, Furqan; Bajwa, Obaid (Journal of University Medical & Dental College, 2024)
BACKGROUND & OBJECTIVE: Ragpickers are free-lancer workers who wander throughout the day, or for the time that suits them to pick and gather recyclable waste materials from streets, wastebins and sell these items to various scrapyards which compensate them with a minimal amount. The conditions they work in are very difficult with health hazards around every corner of which they are unaware. To explore the awareness about health hazards among Ragpickers in Lahore. METHODOLOGY: The study was conducted in the slum vicinity near The University of Lahore adjacent to Raiwind, Lahore. The perception of health hazards among Ragpickers was assessed through a proforma before the start of the study. The Snowball technique was used to collect data. An analysis among the same population was done two weeks later after being given awareness about health hazards. RESULTS: The results show that amongst the 150 sample population the awareness level of the subjects increased by 50% about all diseases but the knowledge about personal hygiene practices remained unchanged. The data was analyzed using chi-square and paired sample t-tests with p value <0.05 considered as significant. CONCLUSION: Through health care programs sponsored by government and NGOs, significant improvement in health among Ragpickers could be seen by following simple principles of hygiene.